A mixed variational formulation for a class of contact problems in viscoelasticity. Issue 8 (11th June 2018) - Matei, A.; Sitzmann, S.; Willner, K.; Wohlmuth, B. I.
Abstract : We consider a deformable body in frictionless unilateral contact with a moving rigid obstacle. The material is described by a viscoelastic law with short memory, and the contact is modeled by a Signorini condition with a time-dependent gap. The existence and uniqueness results for a weak formulation based on a Lagrange multipliers approach are provided. Furthermore, we discuss an efficient algorithm approximating the weak solution for the more general case of a two-body contact problem including friction. In order to illustrate the theory we present two numerical examples in 3D.